Proposed new interior design scheme of Malay Musical Instruement Museum at No 1 A, Jalan Kota, 75000, Bandar Hilir, Melaka for Perbadanan Muzium Melaka / Muhammad Akmal Hakim Ahmad Bajuri - Ahmad Bajuri, Muhammad Akmal Hakim (Faculty of Architecture, Planning and Surveying, 2012)
Malay Musical Instrument Museum is proposed on the basis of awareness among the local community and promote the rural community of musical history in Malaysia. According to the book ‘Muzik dan Nyanyian Tradisi Melayu’ who was written by Haji Aziz Deraman and Wan Ramli Wan Mohamad ,malay instruments has been seen as a heritage and artifacts seen as present. Besides that,museum usually functions to give education, and gives some experiences when enter the spaces. Malaysian musical instrument also refer to the traditional instrument which had been use by the Malaysian over a decade but local people still not know about the malay instruments because of their interested on modem instrument.